Effect of Moisture Content on the Viability and Storability of Azadirachta indica A. Juss (Neem) Seeds - Gurudev Singh, B.; Mahadevan, N. P.; Shanthi, K.; Manimuthu, L.; Geetha, S. (Indian Forester, 1997)
Two methods of drying neem seeds were followed viz. sun drying and shade drying and found that the any of these two methods can be followed for drying seeds. The reduction in seed moisture has not affected the germination per cent. Storing seeds with high moisture content in deep freeze condition had deleterious effect on the viability. Storing seeds with low moisture content in ambient and refrigerator condition was recommended.